Find the inverse function of f.

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

f(x) = 

7 + 9x
5 − 6x
f−1(x) = 
Feb 28th, 2015

answer:

I set y = f(x), so I can write:

y = (7+9x)/ (5-6x)

then:

f^-1(y) = (5y-7) / [3(2y+3)]

Feb 28th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Feb 28th, 2015
...
Feb 28th, 2015
Jun 24th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer